2021
DOI: 10.1016/j.jbc.2021.101208
|View full text |Cite
|
Sign up to set email alerts
|

Receptor binding, immune escape, and protein stability direct the natural selection of SARS-CoV-2 variants

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(83 citation statements)
references
References 75 publications
6
77
0
Order By: Relevance
“…An alternative explanation for positive selection of mutations within the RBD of SARS-CoV-2 is enhancement of resistance to postvaccinated sera [ 24 ]. Studies testing monoclonal antibodies isolated from SARS-CoV-2-vaccinated individuals have demonstrated resistance conferred by nearly all RBD mutations [ 19 , 25 , 26 , 27 , 28 ] ( Figure 3 d). This is not surprising as 40% of the antibodies produced against SARS-CoV-2 target the RBD, and the vast majority of these antibodies are neutralizing antibodies [ 29 ].…”
Section: Mutations Of the S1 Subunit Containing The Receptor-binding ...mentioning
confidence: 99%
“…An alternative explanation for positive selection of mutations within the RBD of SARS-CoV-2 is enhancement of resistance to postvaccinated sera [ 24 ]. Studies testing monoclonal antibodies isolated from SARS-CoV-2-vaccinated individuals have demonstrated resistance conferred by nearly all RBD mutations [ 19 , 25 , 26 , 27 , 28 ] ( Figure 3 d). This is not surprising as 40% of the antibodies produced against SARS-CoV-2 target the RBD, and the vast majority of these antibodies are neutralizing antibodies [ 29 ].…”
Section: Mutations Of the S1 Subunit Containing The Receptor-binding ...mentioning
confidence: 99%
“…The choice of the buffer composition was dictated by the stability of the proteins. Even though these conditions are not optimal for a CD study, they allowed us to assess that the refolded protocol we devised to obtain the SARS-CoV-2 RBD from E. coli worked and that the produced RBDs were folded in those conditions, as indicated (i) by the similarity of the overall far-UV-CD shape with what previously reported for HEK, insect and E. coli RBDs [ 21 , 32 , 41 ], (ii) by the overall consistency in the distribution of the secondary structure composition of the proteins and (iii) by the agreement of the calculated melting temperatures with those reported in the literature in equivalent ionic strength conditions [ 21 ]. Notably, we can exclude an effect of the presence of TCEP on the differences observed between the CD spectra of E. coli -RBD and the ones of HEK-293- and Insect-RBDs, since the spectrum profile of the RBD from E. coli reported in Mycroft-West et al [ 32 ] was obtained in the absence of the reducing agent.…”
Section: Discussionmentioning
confidence: 99%
“…Structure predictions revealed that N500Y may play a significant role in virus binding to ACE2. The K417T and E484K may enhance viral expression and enable the virus to escape from the human immune system [ 27 ]. The Gamma variant revealed a 1.7- to 2.4-fold higher degree of transmission compared to the non-P.1 variants [ 26 ].…”
Section: Virus Variants Of Concern (Vocs) and Former Vocsmentioning
confidence: 99%